The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/en15062199
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic-Based Load Frequency Control in an Island Hybrid Power System Model Using Artificial Bee Colony Optimization

Abstract: This study presents the implementation of Artificial Bee Colony (ABC) optimization in an island hybrid power system model using fuzzy logic-based load frequency control. The Island Hybrid Power System considered in this study consisted of various generation units and an energy storage system. The optimized control parameters of PID using ABC were used in an intelligent fuzzy logic controller. The profiles (power & Frequency) of isolated hybrid power system were improved using a Super Conducting Magnetic En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 29 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Additionally, they offer the ability to control nonlinear systems to a level that surpasses the capabilities of conventional linear control systems. [24].…”
Section: Modelling Of Pv Systemmentioning
confidence: 99%
“…Additionally, they offer the ability to control nonlinear systems to a level that surpasses the capabilities of conventional linear control systems. [24].…”
Section: Modelling Of Pv Systemmentioning
confidence: 99%
“…A novel meta heuristic, derivative-free method named as a quasi-oppositional harmony search algorithm was used to improve the frequency stability in hybrid power systems [11]. Furthermore, sliding mode control [12,13], the bacterial foraging algorithm [14], artificial bee colony algorithm [15], etc., are used to overcome the FD problems in isolated hybrid power systems.…”
Section: Introductionmentioning
confidence: 99%
“…A type 2 fuzzy PID controller for frequency control in hybrid distributed power systems was presented by the authors in [17]. A model of an island hybrid power system that uses artificial bee colony optimization for fuzzy logic-based load frequency management was described by the authors in [18]. The authors in [19] suggested a novel scaling factorbased fuzzy logic controller for frequency regulation of an isolated hybrid power system.…”
Section: Introductionmentioning
confidence: 99%